2012
DOI: 10.1007/s10867-012-9261-0
|View full text |Cite
|
Sign up to set email alerts
|

First principles investigation of L-alanine in terahertz region

Abstract: Terahertz absorption spectrum (0.5-4.0 THz) of L-alanine in the solid phase was measured by terahertz time-domain spectroscopy at room temperature. Simulations utilizing gaseous-state and solid-state theory were performed to determine the origins of the observed vibrational features. Our calculations showed that the measured features in solidstate materials could be well understood by considering the crystal packing interactions in a solid-state density functional theory calculation. Furthermore, intermolecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 33 publications
2
10
0
Order By: Relevance
“…20 The calculated lattice constants (a, b and c) for CH 3 CHNH 2 COOH, CH 2 FCHNH 2 COOH and CHF 2 CHNH 2 COOH are listed in Table 1. It is clear from the table that our theoretical results are in agreement with the reported experimental results 19,21,3,22 for CH 3 CHNH 2 COOH and CH 2 FCHNH 2 COOH, respectively, while no literature 1650079-3 S. Ahmad et al Table 2. Bond lengths (Å) of L-alanine, monoflouroalanine and difluoroalanine.…”
Section: Structural Propertiessupporting
confidence: 88%
“…20 The calculated lattice constants (a, b and c) for CH 3 CHNH 2 COOH, CH 2 FCHNH 2 COOH and CHF 2 CHNH 2 COOH are listed in Table 1. It is clear from the table that our theoretical results are in agreement with the reported experimental results 19,21,3,22 for CH 3 CHNH 2 COOH and CH 2 FCHNH 2 COOH, respectively, while no literature 1650079-3 S. Ahmad et al Table 2. Bond lengths (Å) of L-alanine, monoflouroalanine and difluoroalanine.…”
Section: Structural Propertiessupporting
confidence: 88%
“…They concluded that vibrations in low frequencies are mainly from the twisting and rocking motions of intermolecular hydrogen bonds. First principle calculation of the THz spectrum (16.6 -133.3 cm 21 ) of L-alanine crystal by Zheng et al [20] confirmed that the intermolecular vibration in crystal is an important contribution to THz absorption. Through investigations on THz spectra of L-Ala n (n ¼ 1, 2, 3, 5) (0 -60 cm 21 ), Ponseca et al [25] found there is a clear difference in low-frequency dynamics between amino acids and polypeptides.…”
Section: Introductionmentioning
confidence: 94%
“…The structural differences between amino acids depend on the side chain R and its polarity. Most THz biomolecule investigations have been focused on amino acids in the low-frequency spectral interval [118][119][120][121][122][123][124][125][126][127][128][129][130][131], see Table 1. All 20 standard α-amino acids under the same conditions revealed a correlation between molecular structures and spectral peaks between 0.2 and 3.0 THz (6.67-100 cm −1 ) [122].…”
Section: Current Status Of Thz Spectroscopy For Research On Amino Aci...mentioning
confidence: 99%
“…The amino acids were studied in the solid phase, mixing them with a polyethylene powder in various proportions. For example, high proportions of amino acids to polyethylene (1:1 and 2:1) [123,124], as well as low proportions (1:15 and 1:9) [125,126], are used. From these, it emerged that the proportion of amino acids to THz transparent material in the production of the pellet influences the spectrum, especially in the low-frequency region [123,127].…”
Section: Current Status Of Thz Spectroscopy For Research On Amino Aci...mentioning
confidence: 99%
See 1 more Smart Citation